STORY BY JOHN SEARLES CALLED "A LIST OF LIES" (Ta'limning zamonaviy transformatsiyasi, 2024)
The brief story "A List of Lies" by John Searles examines the grave effects of lying on a person's identity and relationships in an emotionally charged piece. Through the lead character Jane, Searles explores the difficulties of leading a life full of lies and the difficult path to discovering the truth. The objective of this essay is to present a thorough study of "A List of Lies," looking at the main ideas, character relationships, and narrative technique that make this tale an engaging look at the human condition. The opening scene of "A List of Lies" features Jane, a young lady, thinking back on all the lies that have influenced her life. Her quest to unravel these lies and face the realities that lie behind them forms the central theme of the narrative. Jane's existence is a labyrinth of falsehoods, some of which she has told herself to keep herself safe and others of which have been told to her, frequently to keep her from facing the hard facts of reality. The depth and complexity of these lies are gradually exposed through Jane's relationships with her family, friends, and romantic partners as the story progresses. The story's denouement reveals a startling truth about Jane's identity, forcing her to reconsider her previous choices and rewrite her future.